Feasibility of establishing a waste recycling plant in the north of Najaf city and supporting the sustainable environment - Alfadhel, Ali Abdulhussein Khaleel; Ali, Maher Naji; Alfadhal, Fadhal A.; Alshimaysawe, Usamah AAlkarim AAlmunam (Edelweiss Applied Science and Technology, 2024)
The increase in population growth, industrial progress in various fields, rising income, and improved living standards have led to societal development, and consequently, an increase in consumer needs and demands. This has resulted in irrational resource consumption and a significant increase in waste quantities, posing a major threat to the environment and human health, this research came as an attempt to enhance sustainability, create investment opportunities, solve the problem of resource shortages, and eliminate waste in an emerging country like Iraq. A feasibility study was prepared based on the technical study and conducting meetings with officials in Najaf Governorate. A set of conclusions and recommendations were reached, the most important of which were the following. By reviewing the extracted financial ratios, it became clear that the project has a high economic feasibility that is beyond comparison, and the reason can be justified by the huge amount of waste present in the targeted area, in addition to the fact that Iraq is a new experience in such industries related to sustainable development and an industry that provides resources and raw materials for other industries that are considered of great importance and are in demand in Iraq and other neighboring countries, The most important recommendations were Starting to refer the project to an investment company according to the government conditions of the Najaf Governorate Investment Authority and generalizing the successful experience to the governorates of Iraq, and giving this project the utmost importance when compared to other projects as it provides the basic and important resources for local industries, and this is consistent with Iraq’s strategy of focusing on industry and establishing industrial cities.